2016
DOI: 10.1155/2016/3878740
|View full text |Cite
|
Sign up to set email alerts
|

Chongcao‐Shencha Attenuates Liver and Kidney Injury through Attenuating Oxidative Stress and Inflammatory Response in D‐Galactose‐Treated Mice

Abstract: The Chongcao-Shencha (CCSC), a Chinese herbal compound formula, has been widely used as food material and medicine for enhancing physical strength. The present study investigated the possible effect of CCSC in alleviating the liver and kidney injury in D-galactose- (D-gal-) treated mice and the underlying mechanism. Mice were given a subcutaneous injection of D-gal (200 mg/kg) and orally administered CCSC (200, 400, and 800 mg/kg) daily for 8 weeks. Results indicated that CCSC increased the depressed body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Furthermore, the serum levels of ALT, AST, and ALP are widely used to evaluate liver functions, in which ALP plays a very important role in the dephosphorylation of protein enzymes, while ALT and AST are the earliest and most sensitive indicators of liver injury. Meanwhile, UA and CREA are the main indicators of renal function, which will be filtered out through the glomerular fluid into the blood stream in large amounts when renal damage occurs during the aging process [ 37 , 38 ]. Accompanied with oxidative tissue damage of mice liver and kidney, the serum levels of ALT, AST, and ALP, as well as CREA and UA in the model group mice, were significantly higher than those of normal group mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the serum levels of ALT, AST, and ALP are widely used to evaluate liver functions, in which ALP plays a very important role in the dephosphorylation of protein enzymes, while ALT and AST are the earliest and most sensitive indicators of liver injury. Meanwhile, UA and CREA are the main indicators of renal function, which will be filtered out through the glomerular fluid into the blood stream in large amounts when renal damage occurs during the aging process [ 37 , 38 ]. Accompanied with oxidative tissue damage of mice liver and kidney, the serum levels of ALT, AST, and ALP, as well as CREA and UA in the model group mice, were significantly higher than those of normal group mice.…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, VE, the monomer of which is often used as the positive control for the studies of subacute aging in mice induced by d -gal, is a well-known fat-soluble vitamin with excellent antioxidant activity [ 37 , 39 , 40 ]. Given that VE showed no prominent promoting effect on these d -gal-produced reduction of immune function indicators of mice, it was reasonable to infer that the certain protective effect of VE on the liver and kidney of d -gal-induced aging mice might be mainly due to its anti-oxidation quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the specific distribution in the kidney, COX-2 is of vital importance in regulating renin release and water/salt metabolism [ 34 ]. More importantly, the significant role of COX-2 in kidney diseases, especially in CKD, has been documented by using COX-deficient mouse models or COX antagonists [ 35 42 ]. It is known that inhibition of COX-2 is associated with AKI incidence due to the imbalance of renal function in fluid excretion and intra-renal hemodynamics.…”
Section: Cox S In Kidney Diseasesmentioning
confidence: 99%
“…What is more, in traditional Chinese medicine theory, kidney supports human body to be young and vigorous. Our team [15] and other researchers [16] have reported that CS has good antiaging effect through improving antioxidant capacity of aged mice induced by D-galactose. It attracts our attention to reveal if CS can prevent exogenous senescence.…”
Section: Introductionmentioning
confidence: 99%